1983
DOI: 10.1002/aic.690290405
|View full text |Cite
|
Sign up to set email alerts
|

Gas separation by permeators with high‐flux asymmetric membranes

Abstract: The permeation behavior of the high-flux asymmetric membrane differs from that of the conventional symmetric membrane. A calculation method for predicting the gas separation performance of a permeator with asymmetric membrane is presented. The model takes into account the permeate pressure drop and is applicable to both hollow-fiber and spiral-wound modules. The effect of permeate-feed flow pattern on module performance is analyzed. It is shown that for the high-flux asymmetric membrane, the countercurrent flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
91
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 11 publications
2
91
0
1
Order By: Relevance
“…We have shown that the approximate model compares favorably with the fundamental model in terms of prediction accuracy [21]. The major advantage of the approximate model is that the nonlinear algebraic equations can be solved 200± 400 times faster than the fundamental differentialalgebraic-integral equations using the shooting method [24].…”
Section: Spiral-wound Permeator Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…We have shown that the approximate model compares favorably with the fundamental model in terms of prediction accuracy [21]. The major advantage of the approximate model is that the nonlinear algebraic equations can be solved 200± 400 times faster than the fundamental differentialalgebraic-integral equations using the shooting method [24].…”
Section: Spiral-wound Permeator Modelmentioning
confidence: 97%
“…In this section, we describe an approximate model which is derived directly from a fundamental cross-¯ow model [24] by assuming that the residual¯ow rate is constant in the direction of permeate¯ow. The approximate crossow model is suf®ciently accurate for spiral-wound permeators.…”
Section: Spiral-wound Permeator Modelmentioning
confidence: 99%
“…It is also necessary to observe that the concentration of the permeate exiting the membrane coated surface, Y I is not the same as the bulk permeate leaving the porous layer, Y i . However both flows are equal at the end of the membrane [5].…”
Section: Introductionmentioning
confidence: 99%
“…A mathematical model was developed for multicomponent gas separation, which needs previous information of dispersion and diffusion coefficients in the fluid phase and mass transfer coefficient in the porous substrate [15] [17], and the numerical solution was expressed as an initial value problem. But, the overall material balance for co-current flow was used as an approximation for that of countercurrent flow for easy integration into AspenPlus.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of binary gas mixtures the governing equations are solved by asymptotic solutions in a cross flow approach depended on the Navier-Stokes equations. But, these methods do not actually ease the numerical problems but somewhat at low permeabilities the results look to be inaccurate [14].A mathematical model was developed for multicomponent gas separation, which needs previous information of dispersion and diffusion coefficients in the fluid phase and mass transfer coefficient in the porous substrate [15] [17], and the numerical solution was expressed as an initial value problem. But, the overall material balance for co-current flow was used as an approximation for that of countercurrent flow for easy integration into AspenPlus.…”
mentioning
confidence: 99%